Revisiting Integrity: A Comparative Analysis of Conventional and Islamic Perspectives - Zakaria, Azzarina (Journal of Islamic, Social, Economics and Development, 2025)
Integrity is universally acknowledged as a fundamental value throughout cultures; however, its meanings differ based on the moral context in which it exists. This paper provides a conceptual explanation of integrity by integrating two significant perspectives: conventional secular and Islamic. Conventional thought regards integrity as the alignment between values and behaviours, highlighting autonomy, consistency, accountability, and professional responsibility. From the Islamic viewpoint, integrity is defined by amanah (trust) and sidq (truthfulness), emphasising it as both a religious obligation and an inherent trait of character. The two perspectives emphasise the importance of truthfulness, trustworthiness, and integrity for leadership and organisational legitimacy, yet they differ in their foundations; secular anchors integrity in human autonomy, whereas Islamic views integrity within the context of divine accountability. By integrating these perspectives, the paper illustrates that integrity serves as both a personal virtue and an institutional necessity. This paper enhances contemporary scholarly conversation by demonstrating how integrity can function as a unifying virtue in both secular and religious contexts, with practical consequences for leadership credibility, organisational trust, and ethical involvement.